2015
DOI: 10.1371/journal.pone.0138138
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for the Convergence Model: The Emergence of Highly Pathogenic Avian Influenza (H5N1) in Viet Nam

Abstract: Building on a series of ground breaking reviews that first defined and drew attention to emerging infectious diseases (EID), the ‘convergence model’ was proposed to explain the multifactorial causality of disease emergence. The model broadly hypothesizes disease emergence is driven by the co-incidence of genetic, physical environmental, ecological, and social factors. We developed and tested a model of the emergence of highly pathogenic avian influenza (HPAI) H5N1 based on suspected convergence factors that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 73 publications
(138 reference statements)
0
23
0
Order By: Relevance
“…Finucane, Nghiem, et al, 2014) or quantitatively (e.g. Saksena et al, 2015); since one of our goals is to provide precise policy recommendations at a national level, we have used the latter approach. The data discussed here were made possible by National Science Foundation (grant # 0909410) and facilitated through close collaboration with Vietnam's Ha Noi University of Agriculture.…”
Section: Methodsmentioning
confidence: 99%
“…Finucane, Nghiem, et al, 2014) or quantitatively (e.g. Saksena et al, 2015); since one of our goals is to provide precise policy recommendations at a national level, we have used the latter approach. The data discussed here were made possible by National Science Foundation (grant # 0909410) and facilitated through close collaboration with Vietnam's Ha Noi University of Agriculture.…”
Section: Methodsmentioning
confidence: 99%
“…Viet Nam's GIS commune level shapefile was made available to us through another project along with other common geographical layers (roads, rivers, etc.) (Saksena, Fox, Epprecht, et al 2015).…”
Section: Data Sourcesmentioning
confidence: 99%
“…By extension of this logic, we recommend that even future studies of urban fuel use should aim to differentiate between modern urban places and the less modern urban places (Saksena, Fox, Spencer, et al 2014). For a few health outcomes previous studies have shown that the rural-urban dichotomy paradigm is either not valid or is not a refined way of examining the true effects of urbanization and modernization (Allender, Foster, Hutchinson, et al 2008;Allender, Wickramasinghe, Goldacre, et al 2011;Allender, Lacey, Webster, et al 2010;Coogan, White, Evans, et al 2011;Dahly and Adair 2007;Jones-Smith and Popkin 2010;McDade and Adair 2001;Novak, Allender, Scarborough, et al 2012;Riha, Karabarinde, Ssenyomo, et al 2014;Saksena, Fox, Epprecht, et al 2015). We believe then that for all the health effects too associated with the use of cooking fuels the same would hold.…”
Section: Conclusion and Policy Relevancementioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Rabl et al, 2009) Language (Ramakrishnan et al, 2009) Not relevant outcomes (Ramey et al, 2014) Not relevant outcomes (Ramis et al, 2014) Not relevant outcomes (Rauw et al, 2012) Not relevant outcomes (Rauw et al, 2011) Not relevant outcomes (Rawdon et al, 2010 (Sakoda et al, 2012) Territory (Saksena et al, 2015) Territory (Salman, 2009) Not relevant outcomes (Sansyzbay et al, 2013) Study population (Sarikaya and Erbaydar, 2007) Study population (Sartore et al, 2010) Not relevant outcomes (Schmitz et al, 2013) Not relevant outcomes (Schroeer et al, 2009) Not relevant outcomes (Schroeer et al, 2011) Not relevant outcomes (Schultsz et al, 2009) Study population (Schweiger and Buda, 2013) Language Study population (Senne, 2010) Territory The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Citation Reason Of Exclusionmentioning
confidence: 99%